2020
DOI: 10.1021/acsnano.9b09754
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced In-Plane Thermal Conductance of Thin Films Composed of Coaxially Combined Single-Walled Carbon Nanotubes and Boron Nitride Nanotubes

Abstract: Carbon nanotubes (CNTs) and boron nitride nanotubes (BNNTs) are one-dimensional materials with high thermal conductivity and similar crystal structures. Additionally, BNNTs feature higher thermal stability in air than CNTs. In this work, a single-walled carbon nanotube (SWCNT) film was used as a template to synthesize a BNNT coating by the chemical vapor deposition (CVD) method to form a coaxial heterostructure. Then, a contact-free steady-state infrared (IR) method was adopted to measure the in-plane sheet th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 51 publications
3
44
0
Order By: Relevance
“…Compressive strength and shape recoverability of CNT forests can be enhanced, owing to the synergistic effect between the CNTs and outer BNNT coating, [153] while thermal conductance of drydeposited SWCNT films was enhanced without much sacrificing their electrical conductance (Figure 9g). [154] As graphene-based electronics and physics have been fueled by h-BN as a support, the same should be expected for the 1D heterostructures consisting of CNTs and BNNTs. Several challenges are, however, still to be resolved for device applications of such materials: such as a uniform BN coating over the entire length of the CNTs and a good electrical contact between the metal and the inner CNTs through the BN layers.…”
Section: Heterostructures Of Carbon Nanotubes Coated By Hexagonal Boron Nitridementioning
confidence: 85%
“…Compressive strength and shape recoverability of CNT forests can be enhanced, owing to the synergistic effect between the CNTs and outer BNNT coating, [153] while thermal conductance of drydeposited SWCNT films was enhanced without much sacrificing their electrical conductance (Figure 9g). [154] As graphene-based electronics and physics have been fueled by h-BN as a support, the same should be expected for the 1D heterostructures consisting of CNTs and BNNTs. Several challenges are, however, still to be resolved for device applications of such materials: such as a uniform BN coating over the entire length of the CNTs and a good electrical contact between the metal and the inner CNTs through the BN layers.…”
Section: Heterostructures Of Carbon Nanotubes Coated By Hexagonal Boron Nitridementioning
confidence: 85%
“…Using nanotubes ( e.g ., CNTs, BN or WS 2 ) as templates can greatly boost the synthesis of new phase 1D materials from 2D materials. [ 47 ]…”
Section: Controlled Synthesis Of One‐dimensional Hybrids With the Template Of Carbon Nanotubesmentioning
confidence: 99%
“…For example, the BN wrapped CNTs were used as a high power‐tolerant saturable absorber and are believed to have a significantly higher optical damage threshold as well as a great potential for various high‐power optical applications. [ 47‐49 ] The isolated molybdenum sulfide nanowires are believed to exhibit torsional motion not seen in the bulk, and thereby change their bandgap depending on their torsional angle, allowing potential applications in electro‐mechanical switching devices. [ 50 ]…”
Section: Introductionmentioning
confidence: 99%
“…The h-BN proved an effective inltrating material for the CNT array since (i) it can reduce the array air fraction because of radial thickening from the h-BN coating, (ii) the CNT maintains its original thermal conductance and (iii) the h-BN itself is equally an excellent heat conductor that adds additional pathways for heat conduction. 23,104 CNT@BN heteronanotubes offer a highly promising alternative to pure CNT assemblies as TIMs. However, although Jing et al, demonstrated a $50% improvement in thermal conductivity of their VA-CNTs subsequent to h-BN coating, a much greater increase on the order of several magnitudes is still necessary to meet the urgent demands of the electronics industry.…”
Section: Thermal Interface Materials (Tims)mentioning
confidence: 99%
“…20 h-BN sheaths may also enhance the mechanical robustness and provide additional thermal conduction pathways along the CNT axis. [21][22][23] The emergent properties of CNT@BN heteronanotubes lend to their proposed applications as reinforcement llers in high temperature ceramic/metal matrix composites, energy dissipating devices, nanocables, high density interconnects, thermal interface materials, thermal management polymer composites and eld emitters.…”
Section: Introductionmentioning
confidence: 99%